Immunophenotypic and prognostic analysis of PAX8 and TTF‐1 expressions in neuroendocrine carcinomas of thymic origin: A comparative study with their pulmonary counterparts. Issue 6 (20th October 2016) - Bi, Yalan; Deng, Yinghui; Li, Shanqing; Zhou, Xiaoyun; Chen, Yeye; Ma, Dongjie; Mao, Xinxin; Guan, Yuzhou; Chen, Jie; Meng, Yunxiao
Abstract : Objectives: To investigate the immunoreactivity of TTF‐1 and PAX8 in neuroendocrine carcinoma of thymic (TNEC) and pulmonary origins (PNEC), and whether their immunophenotyping could be used to distinguish between NEC of the two sites, as well as prognosis of patients with TNEC. Methods: Twenty‐two cases of TNEC and 20 cases of PNEC were selected for immunohistochemical analysis using PAX8 and TTF‐1. Clinical data and follow‐up information were obtained for survival analyses. Results: TTF‐1 immunoreactivity was seen in 19 PNEC cases (95%) and 13 TNEC cases (59.1%). PAX8 was negative in all pulmonary tumors while positive in 19 thymic cases (86.4%). TTF‐1 positivity was associated with high sensitivity but low specificity for PNEC, and adding PAX8 negativity significantly increased the specificity. PAX8 positivity alone showed essentially 100% specificity and 86.4% sensitivity for TNEC. Survival analysis showed lung metastasis as a significant prognostic factor in TNEC. Conclusion: Our study demonstrated that TTF‐1/PAX8 immunophenotyping may be helpful for differential diagnosis of NECs of pulmonary and thymic origins. TTF‐1+/PAX8− immunophenotyping showed high specificity for PNECs, while PAX8+ alone showed a good diagnostic accuracy for TNEC. Lung metastasis was a predictive factor that associated with survival of TNEC patients. J. Surg. Oncol. 2016;114:697–702 . © 2016 Wiley Periodicals, Inc.